The Effect of Financial Literacy, Access to Capital, Entrepreneurial Orientation, and Market Orientation on the Growth and Sustainability of Micro and Small Enterprises in Palembang - Zulfadhli, Zulfadhli; Desfitrina, Desfitrina; Pramajaya, Jamilah (Eastasouth Institute, 2024)
This study examines the impact of financial literacy, capital accessibility, entrepreneurial orientation, and market orientation on the growth and sustainability of Micro and Small Enterprises (MSEs) in Palembang. Using quantitative analysis on a sample of 170 MSEs and Structural Equation Modeling - Partial Least Squares (SEM-PLS), the results show that these factors significantly influence the success of MSEs. Financial literacy enhances entrepreneurial thinking and market orientation, while access to capital supports both. This study highlights the importance of improving financial knowledge, increasing access to funding, and adapting to market conditions to foster MSE growth. These insights are valuable for policymakers, financial institutions, and businesses.